Gerakan Keberagamaan Baru: Mitosis dan Reflikasi Pantekosta Amerika ke Indonesia - Elia Tambunan; Samuel Kelvin Ruslim (Sekolah Tinggi Teologi Injili dan Kejuruan (STTIK) Kupang, 2021)
It is a historical problem if the Pantecostal Church in Indonesia is generalized as a direct result of the Azusa Street global Pentecostal movement. The academic argument of this paper explains, that church, (where W.H. Offiler and W.W. Patterson are the pioneers from American stream even for other Pentecostals today), has its own wordview and is popular in the American Pacific Northwest, it cannot be generalized. Through literature study research using qualitative source criticism techniques, and by prioritizing primary sources, and using socio-religious movement theory, the answer to why, and in what social setting in America and Indonesia, the ideas of Pantecostalism emerged, here is being presented. This provides a new understanding, the history of the idea of ​​religious man is also the history of the Americanization of Pantecostals in the world and even Indonesia. It should be seen, Pantecostals have their own modes of religiousity in their uniquely enterprises to form a theological identity and religious mode although there are similarities with others. Pantecostal studies with GPdI as the focus of study of transnational religious social movements saving sinners are fit to put in the study of Pentecostalism and global religious studies. Adalah masalah secara sejarah apabila Gereja Pantekosta di Indonesia digeneralisasi sebagai hasil langsung gerakan Pentakosta global Azusa Street. Argumen akademik tulisan ini memaparkan, gereja itu, (di mana W.H. Offiler dan W.W. Patterson sebagai pionir dari arus Amerika bahkan bagi Pentakostal lain hari ini), memiliki wordview sendiri dan popular di Pacific Northwest Amerika tidak bisa disamaratakan. Lewat penelitian studi literatur dengan teknik kritik sumber secara kualitatif, dan dengan mengutamakan sumber primer, serta memakai teori gerakan sosial keagamaan, di sini tersingkap jawaban mengapa, dan dalam latar sosial Amerika dan Indonesia seperti apa ide-ide Pantekosta timbul. Ini memberikan pemahaman baru, sejarah ide tokoh agama adalah juga sejarah amerikanisasi Pantekosta dunia bahkan Indonesia. Perlu dilihat, Pantekosta memiliki mode tersendiri dalam usaha-usaha untuk membentuk identitas teologis dan mode keberagamaan meskipun ada similaritas dengan lainnya. Studi Pantekosta dengan GPdI sebagai fokus kajian dalam gerakan sosial keagamaan transnasional untuk menyelamatkan manusia berdosa tepat dimasukkan ke dalam studi Pentakostalisme dan studi agama global.